Prescription Stimulant Use and Associated Risk Factors for Non-oral Use among 10 to 18 Year Olds. Issue 5 (19th October 2020) - Liu, Yiyang; Smith, Nathan D. L.; Lloyd, Shawnta L.; Striley, Catherine W.; Cottler, Linda B.
ABSTRACT: Non-medical use, especially non-oral use, of prescription stimulants is a public health concern. This study analyzed data from the National Monitoring of Adolescent Prescription Stimulants Study (N-MAPSS). Users (n = 723) were categorized as oral medical only users (n = 330, 45.6%), any oral non-medical users (n = 270, 37.3%), and any non-oral users (n = 123, 17.0%). The associations between patterns of stimulant use and risk factors were examined using logistic regression. Of the 123 any non-oral users, 79 reported using stimulants intranasally and orally, which was the most prevalent pattern of non-oral use. Among any non-oral users, the most common source of stimulants was from school (63.4%). Non-oral users primarily used stimulants to get high (74.4%) compared to 27.1% among other users. Negative consequences significantly associated with any non-oral use but not with oral non-medical use included needing stimulants to "feel ok, " having trouble with teachers, bosses or friends due to stimulant use, and having anxiety and depression symptoms. In this study, non-oral use of prescription stimulants was associated with additional risks of adverse mental health outcomes compared to medical only use and other forms of non-medical use. Stimulant non-oral use interventions should emphasize the risks of intranasal use of stimulants.